1989
DOI: 10.1037/0022-3514.56.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of cooperation and competition and their effects on observers' vicarious emotional responses.

Abstract: The authors express their appreciation to Harry Reis and three anonymous reviewers for their helpful comments on an earlier version of this article. They also gratefully acknowledge Michael Danko's assistance in collecting the data presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
206
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(226 citation statements)
references
References 57 publications
15
206
1
4
Order By: Relevance
“…Nevertheless, the results were quite similar. Responses to others' successes may be either positive or negative and this valence is As already mentioned, there is a substantial amount of literature on the role of attitudes in the formation of empathic responses (e.g., Lanzetta & Englis, 1989). Hareli and Weiner (2002) found a relation between the intensity of negative emotions toward the other and schadenfreude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results were quite similar. Responses to others' successes may be either positive or negative and this valence is As already mentioned, there is a substantial amount of literature on the role of attitudes in the formation of empathic responses (e.g., Lanzetta & Englis, 1989). Hareli and Weiner (2002) found a relation between the intensity of negative emotions toward the other and schadenfreude.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has received some initial support in a substantial number of previous studies showing the important role of pre-existing attitudes in shaping emotional reactions to the plight of others. For example, it is well-documented that positive and negative attitudes toward others strongly moderate empathic responses (Lanzetta & Englis, 1989;Vaughn & Lanzetta, 1980). Our work expands this approach.…”
Section: Balancing Modelmentioning
confidence: 99%
“…In one of the early studies, Lanzetta et al (1989) showed that vicarious fear and distress was markedly lower when the other in pain was disliked 49 . It may be expected that individual difference variables may also account for the variability 40 .…”
Section: Introductionmentioning
confidence: 99%
“…"), a low evaluation of an individual on a trait that is relevant to the calibration of WTRs such as intelligence or physical formidability in men (Harris, 1993;Preston & Kimberley, 1987), and a lack of empathic feelings, i.e. being uninterested in a person's pain or joy (Lanzetta & Englis, 1989). That said, the most common trigger of anger is a cost imposition (Averill, 1982(Averill, , 1983).…”
Section: Triggers Of Angermentioning
confidence: 99%